Correlation of Water Absorption Values of Bitumen Waterproofing Sheets Obtained According to CSN EN 14223 and CSN 503602 - Jan Plachy; Jana Vysoka; Radek Vejmelka; Zdenek Caha (Communications - Scientific letters of the University of Zilina, 2014)
The article deals with the issue of weight water absorption of bitumen waterproofing sheets. It compares two methodologies applicable to examination of water absorption of bitumen waterproofing sheets from the point of view of testing procedures. It compares the results of both the methods for individual bitumen sheets upon experimental measurement and examines mutual relation between the individual results. The experimental measurement was performed on bitumen sheets used for waterproofing of bridge deck [1].